RNA-Seq Analysis of Mouse Hepatocytes AML12 Exposed to Neodymium Nitrate - Ning Wang; Jing Leng; Yaxin Han; Gonghua Tao; Jingqiu Sun; Cheng Dong; Kelei Qian; Xiuli Chang; Ping Xiao; Xinyu Hong (Toxics)
Objective: Neodymium nitrate (Nd(NO3)3) is widely used globally, raising concerns about its occupational and environmental safety. It enters the human body via the digestive system, accumulates in organs, and causes toxicity, including potential hepatotoxicity. However, the role of non-coding RNAs (ncRNAs) in Nd(NO3)3-induced liver injury remains unclear. This study aimed to identify key genes and regulatory pathways involved in Nd(NO3)3-induced hepatic injury using RNA sequencing (RNA-seq) and differential gene expression analysis. Methods: Mouse hepatocytes (AML12 cells) were exposed to Nd(NO3)3, and RNA-seq was performed to analyze the expression profiles of miRNA, lncRNA, circRNA, and mRNA. qPCR was used to validate the RNA-seq results. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were conducted to explore the functions and pathways associated with differentially expressed genes (DEGs). Results: Nd(NO3)3 exposure altered the expression of ferroptosis-related genes and induced significant changes in mRNA, miRNA, circRNA, and lncRNA expression levels. GO and KEGG analyses revealed that DEGs were closely related to cellular ferroptosis pathways. Specific miRNAs, lncRNAs, and circRNAs were significantly upregulated, suggesting their potential as biomarkers for Nd(NO3)3-induced ferroptosis and liver injury. Conclusion: This study provides the first comprehensive transcriptome database for Nd(NO3)3-induced liver injury, highlighting the involvement of ncRNAs in hepatotoxicity. These findings offer valuable insights for developing biomarkers and understanding the mechanisms underlying Nd(NO3)3-induced hepatic injury.